Implementing shaping and differential reinforcement technique in helping children with language difficulty - Wicaksono, Banyu (Psychological Research and Intervention, 2022)
This paper reports on the implementation of shaping and differential reinforcement technique to help a child who struggles in his school activity due to language difficulty. The intervention was conducted in total of 21 session with, 15 main treatment session, 3 session in the beginning of the treatment for baseline measurement and 3 sessions in the end of the treatment for follow-up measurement. Each session lasts 45 to 60 minutes for four weeks. The treatment employs a combination of shaping and differential reinforcement due to the nature of the difficulty faced by the participant. Changes in time spent on assignment and grade was recorded on each session. This study uses single-subject experimental design with baseline as pre-test and follow-up session as post-test. The study participant was Rudi, a boy aged 8. He's a 3rd grade student at local primary school. The result of this study indicates that the intervention program was able to reduce time spent on assignment as the participants is less inclined to do non-assignment related activity or exhibit disruptive behavior compared to baseline. Further, Rudi's grade also showed significant increase during the process and follow-up measurement.